PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI - Ivani, Kartika Aprilia; Lambe, Kristian Hoegh Pride; Irdawati, Irdawati (Accounting Profession Journal (APAJI), 2024)
The Effect of Financial Performance on Stock Prices in Telecommunications Sub Sector Companies Listed on the Indonesia Stock Exchange. The purpose of this study was to determine the effect of financial performance on stock prices in telecommunications sub-sector companies listed on the Indonesian stock exchange. This study used a sample of 8 companies. The test used to test this research is the classical assumption test which consists of multicollinearity test, autocorrelation test, and heteroscedasticity test. Multiple linear analysis and hypothesis testing consisting of the coefficient of determination and partial t test. The results showed that partially the Total Assets Turnover (X1) variable had a positive and significant effect on Stock Prices(Y), the Dept to Equity Ratio variable (X2) had a negative and not significant effect on Stock Prices (Y), Return on Assets (X3) had a negative and no effect significant to the Stock Price (Y).